2006
DOI: 10.1590/s1678-58782006000200007
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent momentum and passive scalar transport in supersonic channel flow

Abstract: Direct numerical simulations of compressible turbulent channel flow including passive scalar transport have been performed at five Mach numbers, M, ranging from 0.3 to 3.5 and Reynolds numbers, Re, ranging from 181 to 1030. The Prandtl and Schmidt numbers are 0.7 and 1.0, respectively, in all cases. The passive scalar is added to the flow through one channel wall and removed through the other, leading to an S-shaped mean scalar profile with non-zero gradient in the channel centre. The paper describes the set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
(13 reference statements)
1
9
0
Order By: Relevance
“…Evolution of bulk Mach number MB w (3.1a), ratio of centerline-to-wall static temperatures, and wall-to-theoretical-adiabatic-wall temperatures (3.1e), as a function of centerline Mach numberMCL (3.1d), for various Reynolds numbers, using the present large-box DNS results (Tab. 2) and other available DNS data Friedrich et al 2006;Wei & Pollard 2011a,b). channel case (Coleman et al 1995, Tab.…”
Section: Compressible Channel Flowmentioning
confidence: 96%
See 2 more Smart Citations
“…Evolution of bulk Mach number MB w (3.1a), ratio of centerline-to-wall static temperatures, and wall-to-theoretical-adiabatic-wall temperatures (3.1e), as a function of centerline Mach numberMCL (3.1d), for various Reynolds numbers, using the present large-box DNS results (Tab. 2) and other available DNS data Friedrich et al 2006;Wei & Pollard 2011a,b). channel case (Coleman et al 1995, Tab.…”
Section: Compressible Channel Flowmentioning
confidence: 96%
“…1) covering, although without a systematic variation of both parameters, the range Re τ ∈ [64,344] Friedrich et al 2006;Tamano & Morinishi 2006;Gerolymos et al 2010;Wei & Pollard 2011b) cover the range Re τ ∈ [150, 300] and M CL ∈ [0.35, 2.25], again without systematic variation of both parameters. The spatial resolution of the present large-box (L x ×L y ×L z = 8πδ ×2δ ×4πδ) computations (Tab.…”
Section: Dns Computationsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 This results in significant turbulence anisotropy within the near wake region and explains the very different turbulence amplifications of the turbulence intensities. Direct numerical simulations ͑DNS͒ performed by Friedrich et al 45 have demonstrated that the absolute pressure-strain correlation terms are typically smaller in compressible flows than in corresponding incompressible flows. One might therefore intuitively expect that the energy transfer process due to the pressure-strain correlation terms will diminish with increasing compressibility, thereby suppressing the redistribution of streamwise turbulence energy to the other components.…”
Section: -9mentioning
confidence: 99%
“…Throughout the study, we use the superscript to represent the normalization with , the friction velocity , the friction temperature (denoted as , , is the mean heat flux on the wall), the viscous length scale (denoted as , , ) and the friction scalar , which is defined as (Friedrich et al. 2006) We also use the superscript to represent the normalization with the semilocal wall units, i.e. and .…”
Section: Numerical Simulation Set-upsmentioning
confidence: 99%